Budgetary Impact of Treating Acute Promyelocytic Leukemia Patients with First-Line Arsenic Trioxide and Retinoic Acid from an Italian Payer Perspective - Kruse, Morgan (PLoS One, 2015)
The objective of this study was to estimate the net cost of arsenic trioxide (ATO) added to all-trans retinoic acid (ATRA) compared to ATRA plus chemotherapy when used in first-line acute promyelocytic leukemia (APL) treatment for low to intermediate risk patients from the perspective of the overall Italian healthcare systemA Markov model was developed with 3 health states: stable disease, disease event and death. Each month, patients could move from stable to disease event or die from either state. After a disease event, patients discontinued initial treatment and switched to the other regimen as second-line therapy. Treatment regimens, efficacy and adverse events were derived from published sources and expert opinion; unit costs were collected from standard Italian sources. Clinical outcomes and costs for pre-ATO and post-ATO scenarios were combined with population and product utilization information to calculate the total budgetary impact using a 3-year time horizon; one-way sensitivity analyses were conducted. Three-year cumulative pharmacy costs for ATO+ATRA were €46,700 per-patient versus €6,500 for ATRA+chemotherapy; however, medical costs for ATO+ATRA were €12,300 per-patient versus €30,200 for ATRA+chemotherapy. The total budgetary impact was estimated to be an additional €127,300, €312,500 and €477,800 in the first, second and third years, respectively. The model was most sensitive to changes in the cost of the ATO+ATRA regimen during the consolidation phase. Budgetary impact models are valuable to payers making formulary decisions regarding the access and affordability of new medicines. The cost of treatment analysis showed that pharmacy costs for ATO+ATRA were higher than for ATRA+chemotherapy, while all other evaluated costs were lower for ATO+ATRA treated patients. The average budgetary impact was €305,900 per year overall, representing a 3.5% increase. Further research is needed to determine the cost-effectiveness of ATO+ATRA compared to the current first-line standard of care in APL.